IT Computer Training Programming with PHPRad for Students of Politeknik STIBISNIS Tegal - Budiraharjo, Eko; Firmansyah, Hasbi; Sofyan, Ali; Sari, Nadya Permata (ASEAN Journal of Empowering Community, 2024)
The implementation of community service activities in the form of "IT Computer Programming Training with PHPRad for Students of Politeknik STIBISNIS Tegal." PHPRad is the name of a highly efficient and useful software in the category of web programming products. This software is for creating robust and flexible web-based software. This software provides a set of tools needed to design and build web applications to make building and programming easier than ever. In fact, this software has stipulated that in order to build a robust application with minimal programming knowledge. This product is a tool suitable for professionals as well as a tool suitable for beginners. To get started with the PHPRad software, you must first create a project and then connect it to the database. Then, in the next step, we will start configuring and building the product page. In addition, in the next step, you will be able to use various components and widgets to enhance the performance of your software. The hallmark feature of this software is its simplicity in working with this product. As you know, with the help of this software, you can build software only in the user environment without programming. PHPRad is one of the software/programs in producing web-based information systems that can significantly meet the needs of students and provide added value for achieving the goals and objectives for students. This information system was developed using several applications, namely PHP. Then, XAMPP V.3.2.1 was used to run the Apache web server and PhpMyAdmin as the database server and web browser. This architectural model is very important considering that the users of this system are all students and teachers who need ease in interacting during the teaching and learning process. The design of a Web-Based Information System Using PHPRad and MySql for students of Politenik STIBISNIS Tegal aims to facilitate the information process for all students who are experiencing difficulties in computer programming coding.